Assessing resource consumption at the subnational level: A novel accounting method based on provincial selected material consumption. (8th September 2020) - Xu, Minghao; Chen, Dingjiang; Yu, Yadong; Chen, Zengbo; Zhang, Yupeng; Liu, Bomin; Fu, Yike; Zhu, Bing
Abstract: With considerable progress in material flow analysis (MFA), conducting MFA at the subnational level has become increasingly necessary but is restricted by problems such as domestic trade data deficiency. In this study, a novel material flow indicator—provincial selected material consumption (PSMC)—and its calculation method were proposed to estimate resource consumption mainly by the manufacturing and construction sectors at the subnational level. In order to overcome the restrictions mentioned above, PSMC accounting simplifies the value chain by selecting certain resources (i.e., considering raw materials and intermediate materials while omitting products), placing emphasis on downstream industries that drive material use from a bottom‐up perspective instead of transboundary flows. The reliability and feasibility of PSMC and the corresponding method were verified by using China as a case study and calculating PSMC of 31 provinces across the country. Furthermore, the sum of these values was compared with the result obtained on the national scale by using an economy‐wide MFA database. PSMC could depict the characteristics of subnational level material use. Moreover, the methodology appropriately balanced reliability against feasibility, which is a concerning issue when analyzing material flows at the subnational level. Overall, PSMC can function as a useful tool for sustainable resource management tailored to subnational areas as well as an important reference for policy making.